The Role of Technological Innovation in Increasing Agricultural Sector Productivity - Aquino, Juan; Cruz, Maria (Raudhah Publisher, 2024)
Technological innovation has a crucial role in increasing the productivity of the agricultural sector, but the challenges in the application of technology in this sector are still quite large. This study explores how technological innovations can affect agricultural productivity and identifies key factors that support or hinder the application of these technologies. The purpose of this study is to understand the impact of technological innovation on agricultural productivity and provide recommendations for the effective use of technology in this sector. The research method used is a qualitative approach with literature studies and in-depth interviews with farmers, agricultural experts, and technology developers. Data was collected through semi-structured interviews and document analysis to gain in-depth insights into technology implementation and challenges faced in the field. The results show that technological innovations such as smart irrigation systems, crop monitoring drones, and agricultural management software significantly improve efficiency and crop yields. However, the application of technology faces obstacles such as lack of training, limited access to technology, and high costs. The study concludes that to maximize the benefits of technology, strategies are needed that include increased training for farmers, technology subsidies, and the development of supporting infrastructure. Recommendations for policy and field practices are provided to help improve the adoption and effectiveness of technology in the agricultural sector.